Anti-Aging in the Perspective of Islamic Law - Asep Ramdan Hidayat (Eduvest - Journal of Universal Studies, 2026)
fiqh muʿāmalah and maqāṣid al-sharīʿah. The rapid growth of the anti-aging industry raises critical questions about the halal status of products and their ethical use among Muslims, particularly in Indonesia's expanding beauty and wellness sector. This research analyzes permissible limits of body care (tazyīn) versus altering Allah's creation (taghyīr khalq Allāh), emphasizing intention, context, and benefits. Using a qualitative normative juridical approach, it examines primary Islamic sources (Qur'an, Hadith), fiqh literature, and fatwas. Findings show anti-aging treatments are permissible if free of haram elements, harmless, and sharia-compliant. Specifically: (1) skincare and non-invasive treatments are mubāḥ with halal ingredients; (2) Botox and fillers are allowed for medical or reasonable aesthetic needs without deception; (3) reconstructive surgery is mubāḥ or wājib for trauma, but purely cosmetic is ḥarām or makrūh; (4) stem cell technology is permissible if ethically sourced and therapeutic, but prohibited for embryonic manipulation. The maqāṣid al-sharīʿah framework evaluates practices for preserving health (ḥifẓ al-nafs), dignity (ḥifẓ al-ʿirḍ), and wealth (ḥifẓ al-māl) without greater harm (mafsadat).